2022
DOI: 10.1186/s13027-021-00411-1
|View full text |Cite
|
Sign up to set email alerts
|

The m6A methyltransferase METTL3 affects autophagy and progression of nasopharyngeal carcinoma by regulating the stability of lncRNA ZFAS1

Abstract: Background Nasopharyngeal carcinoma (NPC) is a malignant tumor originating from the epithelial cells of the nasopharyngeal mucosa of the head and neck. The role of long non-coding RNA and RNA methylation in NPC has received increasing attention. Therefore, this study aims to investigate the mechanism of lncRNA ZFAS1 in NPC and its relationship with RNA methylation, providing evidence for targeted therapy of NPC. Methods Microarray arrays were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…A study revealed that the m6A reader YTHDC1 blocked ubiquitination between lncRNA LSG1 and ESRP2 and inhibited the advancement of renal cell carcinoma [ 32 ]. By altering the stability of lncRNA ZFAS1, the m6A methyltransferase METTL3 influenced autophagy and the development of nasopharyngeal cancer cells [ 33 ]. Bioinformatics studies have also indicated the prognostic characteristics of m6A-related lncRNAs in gastric cancer [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study revealed that the m6A reader YTHDC1 blocked ubiquitination between lncRNA LSG1 and ESRP2 and inhibited the advancement of renal cell carcinoma [ 32 ]. By altering the stability of lncRNA ZFAS1, the m6A methyltransferase METTL3 influenced autophagy and the development of nasopharyngeal cancer cells [ 33 ]. Bioinformatics studies have also indicated the prognostic characteristics of m6A-related lncRNAs in gastric cancer [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Insulin like growth factor binding protein 1 (IGFBP1), an important molecule of m6A, has also been shown to promote cell proliferation and metastasis in NPC driven by Myc [15], and WTAP promotes DIAPH1-AS1 can promote the proliferation and invasion of NPC [16]. METTL3 can also promote the development of NPC by promoting the stability of ZFAS1 [17]. circMAP3K4 promotes the development of NPC by regulating its ability to encode small peptides through regulating m6A modification [18].…”
Section: Discussionmentioning
confidence: 99%
“…YTHDF2 captured eIF4G1 transcripts containing m6A and induced mRNA degradation, thereby promoting autophagy and reducing tumor occurrence [ 147 ]. m6A modification enhanced the stability of ZFAS1 [ 148 ]. Lnc RNA ZFAS1 is upregulated in tumor tissues and neural progenitor cells (NPC) [ 148 ].…”
Section: The Regulatory Role Of M6a Modifications In Autophagymentioning
confidence: 99%
“…m6A modification enhanced the stability of ZFAS1 [ 148 ]. Lnc RNA ZFAS1 is upregulated in tumor tissues and neural progenitor cells (NPC) [ 148 ]. ZFAS1 upregulated the expression of ATG10 and regulated autophagy by inhibiting the PI3K/Akt signaling pathway to promote the proliferation and migration of NPC cells [ 148 ].…”
Section: The Regulatory Role Of M6a Modifications In Autophagymentioning
confidence: 99%